An improved optimal control strategy for hybrid AC/DC power system. (October 2018) - Gao, C H; Liu, W M; Zheng, T T; Liu, Z W; Miao, S H; Kang, Y L; Fan, Z H; Liu, Y L; Zhang, M M
Abstract: The additional modulation function of high voltage direct current (HVDC) links can improve the system stability while the unavoidable random external disturbance and sudden changes seriously affect the controller performance and the system stability. In this paper, an improved control scheme based on inverse optimal adaptive control is proposed for the hybrid AC/DC system which considers the system parameter error, external disturbance and other random perturbation. The proposed control scheme combines the inverse optimal control approach and the adaptive control method to account for the modelling errors and uncertainty, which aims at the disturbance attenuation and the optimal operating of the hybrid AC/DC power system. Besides, the improved PI (Proportional-Integral) controller based on the lead-lag link for the current control of HVDC system is proposed to further improve system dynamic performance. Simulations conducted on a typical hybrid AC/DC system show the correctness and validity of the proposed control method.